PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (STUDI KASUS PADA PENGGUNA JASA PENGIRIMAN BARANG KANTOR POS SEMARANG) - Yuni Rosa Indah; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
The success of a company depends on several components that areinterconnected and mutually supportive of one another. These components are thequality of service and customer satisfaction. There are five dimensions ofcharacteristics that can be used to measure and assess the extent to which thecompany is able to provide quality services related to customer satisfaction, namely:reliability, responsiveness, assurance, empathy and tangible.This study aims to identify and analyze how much influence the quality ofservice to the level of satisfaction experienced by customers who use the services ofPost Office Semarang.The study method used in this study is the method of interviews,questionnaires, and literature study using a Likert scale and the sampling methodused was accidental sampling of 100 samples. The analytical method used wassimple and multiple method regression analysis.Based on the result analysis, variable the reliability, responsiveness,assurance, empathy and tangible, have a positive influence of the customersatisfaction. Variable empathy have the most influence is as much as 39,8%.Variable tangible have influence of 39%, Variable reliability have influence of 32,9%,Variable responsiveness have influence of 24,4% and variable assurance haveinfluence of 35,9%. Simultaneously a variable the reliability, responsiveness,assurance, empathy and tangible, having contributions amounting to 72,2% of thecustomer satisfaction.